2013
DOI: 10.1080/00380768.2012.733869
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide mitigation in UK agriculture

Abstract: Nitrous oxide (N 2 O) makes the single largest contribution to greenhouse gas (GHG) emissions from UK and European Union agriculture. Ambitious government targets for GHG mitigation are leading to the implementation of changes in agricultural management in order to reduce these emissions (mitigation measures). We review the evidence for the contribution of those measures with the greatest mitigation potential which provide an estimated 4.3 t CO 2e ha À1 y À1 GHG reduction in the UK. The mitigation options cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 73 publications
1
34
0
1
Order By: Relevance
“…In the particular case of manure, U, and other N synthetic fertilizers incorporation at seeding, NO 3 − losses can be triggered by leaching during high rainfall seasons or irrigation periods (Quemada et al 2013) and also enhance N 2 O emissions when compared to surface applications (Pain et al 1989). These N losses could be minimized by synchronizing N application rates with crop demand through split applications thus avoiding excess of N (Rees et al 2013). As for mechanical incorporation, washing U could favor the presence of reactive N under conditions of higher soil moisture, due to favorable soil conditions for denitrification processes and subsequent high N 2 O emissions (Wrage et al 2001).…”
Section: Trade-offs Of the Mitigation Scenariosmentioning
confidence: 99%
“…In the particular case of manure, U, and other N synthetic fertilizers incorporation at seeding, NO 3 − losses can be triggered by leaching during high rainfall seasons or irrigation periods (Quemada et al 2013) and also enhance N 2 O emissions when compared to surface applications (Pain et al 1989). These N losses could be minimized by synchronizing N application rates with crop demand through split applications thus avoiding excess of N (Rees et al 2013). As for mechanical incorporation, washing U could favor the presence of reactive N under conditions of higher soil moisture, due to favorable soil conditions for denitrification processes and subsequent high N 2 O emissions (Wrage et al 2001).…”
Section: Trade-offs Of the Mitigation Scenariosmentioning
confidence: 99%
“…Despite this lack of understanding of variation in N 2 O emissions, rudimentary management guidelines already exist regarding the timing of fertilizer application (Environment Agency, 2015). These are designed to prevent N losses during rain through leaching and N 2 O emissions but could benefit markedly from a fuller understanding of the processes governing N 2 O fluxes to reduce future emissions (Rees et al, 2013). Currently, IPCC tier 1 emissions factors (EF) guidance states that ca.…”
Section: Introductionmentioning
confidence: 99%
“…A recent continental study identified N 2 O as the single most important greenhouse gas emitted from landbased sources with emissions from Europe equivalent to 97 Tg C yr −1 (Schulze et al, 2009). Agricultural soils used for grassland and arable production are a major source of N 2 O, and strategies to reduce greenhouse gas emissions from the agricultural sector frequently highlight the importance of management interventions (Mosier et al, 1998;Rees et al, 2013). However, the contribution of management to mitigation can be difficult to assess against a background of fluxes that are highly variable in time and space, since emissions vary significantly in response to both climate and local environmental (particularly soil) conditions (Abdalla et al, 2010;Flechard et al, 2007;Skiba and Ball, 2002).…”
Section: Introductionmentioning
confidence: 99%